RADIO KOMUNITAS SEBAGAI TEKNOLOGI TEPAT GUNA UNTUK KOMUNIKASI MASYARAKAT - Rustamaji, Rustamaji; Sawitri, Kania (Jurnal Borneo Saintek, 2023)
At this time there are various types of equipment for electronic communication or often called telecommunications equipment that can be used by the public. Difficulties for students who do not have or master the use of the latest telecommunications equipment, and live in areas that are not covered by telecommunications networks. Of course there must be an appropriate alternative technology that can be used. Where one of them uses broadcast technology through "community radio". Community radio is a radio broadcasting station that is owned, managed, earmarked, initiated, and established by a community. Community radio to disseminate or broadcast information in the form of sound (audio) such as talk, news, or music, through radio waves at a certain frequency. Community radio is useful for distance learning activities, both in situations where there is a pandemic that limits face-to-face activities, or situations without a pandemic, such as overcoming technological limitations in areas that are not covered by cable or cellular telecommunications networks for internet applications.